Myofibroblastic CAF density, not activated stroma index, indicates prognosis after neoadjuvant therapy of pancreatic carcinoma - Heger, Ulrike; Martens, Anna; Schillings, Lisa; Walter, Britta; Hartmann, Domenic; Hinz, Ulf; Pausch, Thomas; Giese, Nathalia; Michalski, Christoph; Hackert, Thilo (Cancers, 2022)
Neoadjuvant therapy (NT) for advanced PDAC is an emerging concept, affecting both stroma and tumor. The Activated Stroma Index (ASI; ratio of activated cancer-associated fibroblasts (CAF) to collagen deposition) is a prognostic marker in upfront resected pancreatic adenocarcinoma (PDAC). We assessed ASI and its prognostic relevance after NT. Tissue from resection specimens of n = 48 PDAC patients after neoadjuvant chemotherapy with FOLFIRINOX (FOL; n = 31), gemcitabine + nab-paclitaxel (GEM; 7) or combination treatment (COMB; 10) was compared with upfront resected matched controls (RES; 69). Activated CAFs were assessed by immunohistochemistry for α-SMA, and collagen was stained with aniline blue; the stained area was then determined by computational imaging analysis and ASI was calculated. In GEM, ASI was significantly higher and collagen deposition lower than in controls and FOL. The lowest quartile of ASI values had significantly longer overall survival (OS) in RES, whereas in FOL, the highest quartile had the best prognosis. After NT, OS was significantly improved in the α-SMA-high group; in RES, however, survival was independent of α-SMA. Reversed prognostic association of ASI thus points to the differing significance of stromal composition after FOL, while improved prognosis with high CAF abundance suggests a synergistic effect of myofibroblasts with chemotherapy. These divergences impede usability of ASI after NT.